Using Blockchain and Cloud Computing Technologies as a Proposed Framework for Improving the Preparation and Presentation of Digital Financial Reports - Mohammed, L.Dr. Rebaz Mohammed Hossein Mohammed; Sultan, Asst.Prof.Dr. Ayad Shaker Sultan (Sulaimani Journal for Humanities, 2026)
This research aims to develop a proposed framework for the integration of blockchain technology and cloud computing as a digital technology innovation to improve the preparation and presentation of digital financial reports. To achieve the research objectives, the researchers adopted the inductive approach as the basis for completing the theoretical aspect of the research by reviewing the concept, importance, and characteristics of the two technologies, as well as discussing their advantages and the challenges of their application in preparing and presenting digital financial reports. To complete the practical aspect, the researchers relied on the deductive approach by proposing a framework for improving digital financial reports in light of the use of cloud blockchain technology. The proposed framework relies on a set of characteristics and advantages available in the two aforementioned technologies, which provides further benefits that contribute to improving these reports. The research concluded with several key findings, most notably that the integration of blockchain and cloud computing represents a promising strategic opportunity to improve digital financial reporting. This is achieved by providing accurate, secure, and highly reliable financial reports, as well as ensuring faster reporting processes and a high level of transparency and disclosure. The research recommended that bank management adopt the proposed framework based on the integration of blockchain and cloud computing technologies in preparing and presenting digital financial reports if it wants to succeed, develop its banking operations efficiently within its sector, and gain the trust of its users and clients as it keeps pace with developments in digital information technology.
Keywords: Blockchain; Cloud Computing; Supporting Technologies; Digital Financial Reporting